Comparison Between Unstablized And Stabilized Soil That Affect Shear Strength Characteristics - Mohamad Haluwi, Muhammad Fadhli; Muhamad Mahir, Muhammad Umar Akashah; Zamri, Mohamad Ilman Hafiz; Mohd Razali, Siti Nooraiin (Multidisciplinary Applied Research and Innovation, 2023)
In civil engineering, clay and peat soils can be classified as problematic soils as they can cause bearing capacity failure such as landslides due to having low shear strength. Therefore, the objective of this study is to understand the shear strength characteristics of the original clay and peat and also to identify the changes of shear strength value in clay and peat after stabilized with polymer. Thus, the workability of the additional Vinyl Acetate Acrulic Copolymer, VAAC, as stabilized agent can be identified. To achieve these objective, the direct shear test was conducted for the original and stabilized clay and peat. This study shown that when clay and peat are mixed with VAAC, their shear strength rises. However, in terms of friction angle, clay combines better with VAAC than peat. In conclusion, this study will understand the shear strength characteristics of clay and peat before and after stabilization with polymers.